How to get the best home loan - Bell, W. Frazier (Wiley, 2001)
Ever-changing mortgage guidelines . . . confusing financial forms . . . if you're buying or refinancing a home, you know all too well how overwhelming and intimidating the mortgage process can be. This revised edition of How to Get the Best Home Loan guides you through all the critical issues and demystifies the mechanics of mortgage lending-everything from disclosures and fees to closing costs, points, and making payments. Longtime mortgage banking industry insider and former realtor W. Frazier Bell helps you sidestep the risks of financing a mortgage and sheds light on many unknown aspects that keep borrowers from making intelligent, money-saving decisions.Written in clear, simple language, this comprehensive Second Edition features new information on desktop underwriting, merged credit reports, and using the Internet, as well as updated sections on verifications, qualifying, and loan types. Bell gives you hands-on access to his hard-won experience, providing the tools you need to: * Understand why lenders do the things they do * Learn what to look for when comparing loans and lenders * Head off potential problems and expensive mistakes * Navigate FRMs, ARMs, FHAs, GEMs, and TILs * Know why certain loans may be better for you than others * Save yourself hundreds, even thousands, of dollars Packed with real-life examples, sample forms, and proven advice, How to Get the Best Home Loan, Second Edition will ensure that you get the right loan, at the right price, from the right lender.